Cardiac Work Remains High after Strength Exercise in Elderly - Queiroz, A.C. C.; Kanegusuku, H.; Chehuen, M. R.; Costa, L.A. R.; Wallerstein, L. F.; Dias da Silva, V. J.; Mello, M. T.; Ugrinowitsch, C.; Forjaz, C.L. M. (International Journal of Sports Medicine, 2013)
Moderate- to high-intensity strength training is recommended for healthy adults. In young subjects, a single session of strength training decreases blood pressure, while heart rate and cardiac work remain elevated afterwards. However, these effects have not been clearly demonstrated in elderly subjects. To investigate this issue, 16 elderly subjects each underwent a Control and an Exercise (3 sets, 8 RM, 9 exercises) session conducted in random order. Haemodynamic variables and heart rate variability were measured before and after the interventions. Systolic blood pressure did not change after the exercise session but did increase after the control session (+8.1±1.6 mm Hg, P≤0.05). Diastolic blood pressure, as well as systemic vascular resistance increased similarly after both sessions. Cardiac output and stroke volume decreased, while heart rate, rate-pressure product and the low- to high-frequency ratio of heart rate variability increased only after the exercise session ( − 0.5±0.1 L/min, − 9.3±2.0 ml,+3.8±1.6 bpm, +579.3±164.1 mmHg.bpm and +0.71±0.34, P≤0.05). Ambulatory blood pressure was similar after both sessions, while heart rate and rate pressure product remained higher after the exercise session for up to 4.5 h. After a single session of strength training, cardiac sympathetic modulation and heart rate remain elevated in elderly subjects, keeping cardiac work elevated for a long period of time.
Keywords: aging; resistance training; cardiovascular load; haemodynamics; ambulatory blood pressure; autonomic modulation